Suitability Analysis of Subsea Pipeline Route using GIS - Matori, A.N (2009)
The objective of this study is to analyze the least cost subsea pipeline routing using GIS. A past pipeline routing project has been adopted in this research as a case study where the GIS-generated pipeline route will be compared with the existing pipeline route designed using contemporary method. Amongst the parameters affecting the pipeline routing includes, submarine geographical features such as seabed conditions and slopes, obstructions such as coral reefs, wildlife preservation areas, as well as availability of existing services such as pipelines and platforms. In order to obtain the best route with the least cost, GIS Spatial Analyst features using cost-weighted distance function was utilized. The result generated has shown similar alignment with the existing route. The GIS-generated route is 0.09km longer than the existing route. Although longer in length, the least cost route crosses less steep areas at length of three times more than the existing route. It crosses prawns’ areas at 4% less than existing route as well. Therefore, the least cost path reduces the construction cost and increases the ease of construction as compared to the existing route. Hence, GIS-generated route satisfies the criteria of economical, least obstructions, safe and ease of construction in producing subsea pipeline route. Comparison between GIS method and contemporary pipeline routing method highlighted unique benefits of GIS that proved its feasibility in pipeline routing improvisation.